Telomere and telomerase in hematological disorders Focusing on bone marrow failure syndromes and hematological malignancies - Mardiah Suci Hardianti; Ibnu Purwanto; Johan Kurnianda (Acta Interna The Journal of Internal Medicine, 2014)
ABSTRACTWe review the present knowledge of telomeres and telomerase with special attention to their role in hematological disorders especially bone marrow failure syndromes including acquired aplastic anemia and myelodysplastic syndromes, as well as acute and chronic myeloid leukemia. The current understanding on the role of telomere and telomeres dysfunctions in hematological disorders leads us to a better understanding on the pathology of the diseases as well as considering some possibilities to employ the measurement of telomere length and telomere activity in disease prognostication. Several treatment options targeting telomere and telomerase being developed are also reviewed.Keywords: telomere- telomerase- bone marrow failure syndromes- hematological malignancies